2020
DOI: 10.3390/en13102471
|View full text |Cite
|
Sign up to set email alerts
|

Geometry-Load Based Hybrid Correction Method for the Pre-Deformation Design of a Steam Turbine Blade

Abstract: To solve the problem of the slow convergence of the geometry-based correction (GC) method in the design of a steam turbine blade, this paper proposes a geometry-load-based hybrid correction (GLHC) method. In this method, the deformation of the blade caused by the centrifugal load is still corrected by the GC method, while the deformation caused by the aerodynamic load is corrected by the load-based correction (LC) method instead of the GC method. The LC method updates the cold shape of the blade by reversely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…They found that the stress on the surface of the blade after considering the effect of the fluid-structure coupling has a significant difference compared with only centrifugal force considered. Yi et al (2020) calculated the deformation of a fan blade under aerodynamic force based on a fluid-structure coupling algorithm and applied the results to predeformation design of the blade. Vinha et al (2020) constructed the governing equations of solid interaction through the strongcoupling and the weak-coupling methods and analyzed the stress and deformation of a certain aero-engine fan blade.…”
mentioning
confidence: 99%
“…They found that the stress on the surface of the blade after considering the effect of the fluid-structure coupling has a significant difference compared with only centrifugal force considered. Yi et al (2020) calculated the deformation of a fan blade under aerodynamic force based on a fluid-structure coupling algorithm and applied the results to predeformation design of the blade. Vinha et al (2020) constructed the governing equations of solid interaction through the strongcoupling and the weak-coupling methods and analyzed the stress and deformation of a certain aero-engine fan blade.…”
mentioning
confidence: 99%